Dose-dependent effects of Asparagus adscendens root (AARR) extract on the anabolic, reproductive, and sexual behavioral activity in rats. (February 2015) - Bansode, Falgun Wanganuji; Arya, Kamal Ram; Singh, Rama Kant; Narender, T.
Abstract Context: Asparagus adscendens Roxb (Liliaceae) has a promising role in modulation of various disorders such as leucorrhea, diarrhea, dysentery, diabetes, senile pruritus, asthma, fatigue antifilarial, antifungal, spermatorrhea, and sexual debility/seminal weakness. Objective: To investigate dose-dependent effects of Asparagus adscendens root (AARR) extract on anabolic, reproductive, and sexual behavioral activities with a view to emphasize the pharmacological basis. Materials and methods: Rats were divided into five groups: Group I (control), Groups II–IV (AARR treated, 100, 200, and 300 mg/kg body weight, respectively, orally for 30 d) and Group V (standard control treated with sildenafil citrate, 5 mg/kg body weight). On day 31, copulatory and potency tests were carried out and an autopsy was done to study the reproductive function, namely, organ weights, spermatogenesis, daily sperm production rate (DSP), and epididymal sperm counts (ESC). Results: AARR extract (200 and 300 mg/kg doses) caused a significant increase in body (p < 0.02 and p < 0.001) and testes (p < 0.01 and p < 0.001, control versus treated) weights. Reproductive activity showed significant a increase in testicular tubular diameter (p < 0.005–0.001), the number of round/elongated spermatids (p < 0.02–0.001), DSP, and ESC (p < 0.05–0.001). The sexual behavioral parameters including mounting/intromission frequency (13.0 ± 0.32/11.8 ± 0.37 and 18.2 ± 2.12/14.8 ± 1.15 versus 11.2 ± 0.66/8.2 ± 1.16), ejaculation latency (187.4 ± 1.91 and 191.4 ± 1.72 versus 180.0 ± 3.47), and penile erections (13.5 ± 0.3 and 14.5 ± 0.5 versus 8.5 ± 0.2) showed a significant increase at 200 and 300 mg/kg doses (ED50 300 mg/kg), but less than a standard control. In contrast, 100 mg/kg dose caused an increase (p < 0.005) in mounting latency only. Conclusion: These results indicate increased anabolic, reproductive, and sexual activities by AARR treatment. Thus, the data provide scientific rationale for its traditional use as an aphrodisiac or for sexual disorders.